Experimental analysis on defect power cable with TDR technique application - Kuan T.M.; Ariffin A.M. (Institution of Engineering and Technology, 2023)
Cable sheathing; Cables; Defects; Insulating materials; Insulation; Joints (structural components); Reflection; Reflectometers; Telecommunication cables; Cable insulation; Experimental analysis; Impedance mismatch; Injected signal; Reflected signal; Reflectometry technique; TDR techniques; Time-domain reflectometry techniques; Time domain analysis